Using Maps to Bridge the Socio-technical Gap: A Practitioner’s Experience Report - Paola Mauri (Complex Systems Informatics and Modeling Quarterly)
In my projects, devoted to the implementation of management systems, it is necessary to take into account several social and technical features and link and merge social and technical environments. To bridge the gap between these environments, maps and mapping are a useful support. In this article these topics are presented through a cluster of projects I developed in large sized companies, where exploring the context is difficult and time consuming and the relationships are structured as a complex network. I focus on the maps that describe relationships between organizational structures and IT technologies; and describe in detail two cases: a success and a failure of my socio-technical approach. The lessons learned are presented and proposed as a reflection on the socio-technical perspective.